PANDANGAN DAN PEMAHAMAN MASYARAKAT KOTA MEDAN HELVETIA TERHADAP ASURANSI SYARIAH : (STUDI DESKRIPTIF PADA MASYARAKAT KOTA MEDAN HELVETIA) - Ahmad Habib Pinim; Fauzi Arif Lubis (INTERNATIONAL, Journal of Sharia Business Management, 2023)
Sharia insurance is an attempt to protect and help each other in accordance with sharia principles. In this study, Islamic insurance was examined by the people of the city of Medan Helvetia on their understanding of Islamic insurance in this modern era. The research objective is to find out the relationship between the views and understanding of the people of Medan Helvetia towards sharia insurance. The method used in this research is descriptive qualitative in the form of observation and interviews. The results of the study found that views and understanding together had a positive and significant effect on the response of the people of Medan Helvetia to sharia insurance and significantly had a real influence on the response of the people of Medan Helvetia to sharia insurance.